Material-Specific Roadmap Modes Can Improve the Visibility of Liquid Embolic Agents for Endovascular Embolization: A Systematic In Vitro Study - Schmitt, N.; Wucherpfennig, L.; Hohenstatt, S.; Karimian-Jazi, K.; Breckwoldt, M.O.; Kauczor, H.-U.; Bendszus, M.; Möhlenbruch, M.A.; Vollherbst, D.F. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Endovascular embolization using liquid embolic agents is a safe and effective treatment option for AVMs and fistulas. Because reliable visibility of these liquid embolic agents is essential for intraprocedural visual control to prevent complications, novel angiographic systems are equipped with material-specific roadmap modes. The aim of this study was the systematic in vitro comparison of conventional and material-specific roadmap modes regarding the visibility of the most used liquid embolic agents.MATERIALS AND METHODS: A recently introduced in vitro model, resembling cerebral vessels, was embolized with Onyx 18, Squid 18, PHIL 25%, and n-BCA mixed with iodized oil (n = 4 for each liquid embolic agent), as well as with contrast medium and saline, both serving as a reference. Imaging was performed in conventional and material-specific roadmap modes. The visibility of the liquid embolic agents in both modes was compared quantitatively and qualitatively.RESULTS: Significant differences between conventional and material-specific roadmap modes regarding the visibility of the liquid embolic agents were observed for all study groups. All liquid embolic agents were better visible in the material-specific roadmap modes compared with the conventional mode in qualitative and quantitative analyses (eg, Onyx in conventional-versus-material-specific modes along the 1.0-mm sector: mean contrast-to-noise ratio, 5.69 [SD, 0.85] versus 47.18 [SD, 5.72]; P < .001, respectively).CONCLUSIONS: In this in vitro study, we demonstrated a better visibility of all investigated liquid embolic agents by using material-specific roadmap modes compared with the conventional roadmap technique. Especially in complex anatomic situations, these novel roadmap modes could improve the visual control and thus the safety and efficacy of embolization procedures in clinical practice.CNRcontrast-to-noise ratioDUdensity unitsLEAliquid embolic agent